Determinants of Egypt's economic growth for the period 1985-2007 - Hammam, Rasha Mostafa (AUC Knowledge Fountain, 2010)
The main aim of this research is to examine the significance of several economic growth determinants to gauge their impact on Egypt's economic growth. This research uses annual time series analysis to assess the significance of several important variables on economic growth in Egypt for the period 1985-2007, and applies Ordinary Least Square method of estimation, with an autoregressive specification. The estimation results reveals positive and significant effect of gross fixed capital formation, foreign direct investment, investment in infrastructure, household consumption expenditure, exports and taxes on international trade on economic growth in Egypt, while the government consumption expenditure shows negative and significant effect on Egypt's economic growth. The main policy implications are the catalytic effect of gross fixed capital formation on economic growth as represented by the public and private investment, in addition, the significance of foreign direct investment in transferring technology, and providing source of finance, where the investment in infrastructure is considered a corner stone for attracting both domestic investments and foreign direct investments and boosting economic development in Egypt. Further, the exports enlarge the domestic capacity utilization and exploit economies of scale. However, the negative significance of government consumption expenditure implies the non productive spending that should be minimized and reallocated to productive spending.